Total leucocytes in human semen of normal and pathologic origin - Shandhan, K. P.; Gusani, P. H. (Investigación Clínica, 2013)
Total Leucocytes were counted by using O-touJidine, in one hundred and thirty nine semen samples of normal and pathological origin.The values of alI the samples had fallen almost in the same range. However significant difference in mean value was 8een in oLigoasthenozoospermia (p < 0.05).